Criminal legalities in the Global South: cultural dynamics, political tensions, and institutional practices - Ciocchini, Pablo Leandro; Radics, George Baylon (Routledge studies in crime and justice in Asia and the Global South, 2020)
Reinterpreting chaos as diversity : an alternative legal approach from the Global South / Pablo Ciocchini -- Criminalizing adultery in Colonial India : constructing the wife vs. the other in Islamic family law / Anisur Rahman -- "First World problems" in the "Third World" : LGBT rights in Singapore / George Radics -- Privacy in public spaces : the transformative potential of Navtej Johar v. Union of India / Danish Sheikh -- Gambling with criminal law : the legal paradox of "Jogo do Bicho" (animal lottery) criminalization in Brazil / João Araújo Monteiro Neto and Nestor Eduardo Araruna Santiago -- (Cr)immigration in the Dominican Republic? : decolonizing the human rights of vulnerable Haitian migrants / Carolina Yoko Furusho -- Cosmologies of federal criminal procedural reform : democratizing and humanizing criminal justice in Argentina / Julieta Mira -- Of punishment, protest, and press conferences : contentious politics amidst despotic decision in contemporary Burmese courtrooms / Elliott Prasse-Freeman -- The politics of judicial actors in the Philippines : war on drugs / Pablo Ciocchini -- Arresting a due process revolution : the reform of Indonesia's code of criminal procedure and the persistence of history / Jayson Lamchek -- Examining premature dismissal rates in Peruvian corruption cases / Wilson Hernández -- Sexual crimes and transitional justice before courts in Brazil : accountability for crimes against humanity / Emilio Peluso Neder Meyer and Claudia Paiva Carvalho -- Seeking commonalities from across the South / George B. Radics.